TRIM65 as a key regulator of ferroptosis and glycolysis in lactate-driven renal tubular injury and diabetic kidney disease - Guangyan Yang; Xiaomai Liu; Yanchun Li; Lixing Li; Jiaqing Xiang; Zhen Liang; Meixiu Jiang; Shu Yang (Cell Reports, 2025)
Summary: Recent studies have highlighted the critical role of renal tubular epithelial cell (TEC) damage in the progression of diabetic kidney disease (DKD), where lactate accumulation is closely associated with TEC injury despite unclear mechanisms. This study demonstrates that TRIM65 knockout exacerbates diabetic kidney damage, while TEC-specific overexpression of TRIM65 ameliorates injury. Mechanistically, TRIM65 suppresses ferroptosis by targeting iron-responsive element binding protein 2 (IREB2) for ubiquitin-mediated degradation while also inhibiting glycolysis through ubiquitination and degradation of pyruvate dehydrogenase kinase 4, a key glycolytic regulator. Notably, lactate promotes p300-mediated lactylation of TRIM65 at lysine 206 (K206), which reduces ubiquitin ligase activity. Supplementation of wild-type TRIM65 reverses kidney damage in knockout mice, and overexpression of the lactylation-defective K206R mutant further enhances protective effects against DKD. These findings reveal that lactate-induced lactylation of TRIM65 at K206 impairs its dual regulatory roles in inhibiting ferroptosis and glycolysis, thereby driving DKD progression and identifying therapeutic targets.